Disparities in treatment and outcome of kidney replacement therapy in children with comorbidities: an ESPN/ERA Registry study - Schild, Raphael; Dupont, Simeon; Harambat, Jérôme; Vidal, Enrico; Balat, Ayşe; Bereczki, Csaba; Bieniaś, Beata; Brandström, Per; Broux, Francoise; Consolo, Silvia; Gojkovic, Ivana; Groothoff, Jaap W; et al. (Clinical kidney journal, 2023)
BACKGROUND: Data on comorbidities in children on kidney replacement therapy (KRT) are scarce. Considering their high relevance for prognosis and treatment, this study aims to analyse the prevalence and implications of comorbidities in European children on KRT. METHODS: We included data from patients <20 years of age when commencing KRT from 2007 to 2017 from 22 European countries within the European Society of Paediatric Nephrology/European Renal Association Registry. Differences between patients with and without comorbidities in access to kidney transplantation (KT) and patient and graft survival were estimated using Cox regression. RESULTS: Comorbidities were present in 33% of the 4127 children commencing KRT and the prevalence has steadily increased by 5% annually since 2007. Comorbidities were most frequent in high-income countries (43% versus 24% in low-income countries and 33% in middle-income countries). Patients with comorbidities had a lower access to transplantation {adjusted hazard ratio [aHR] 0.67 [95% confidence interval (CI) 0.61-0.74]} and a higher risk of death [aHR 1.79 (95% CI 1.38-2.32)]. The increased mortality was only seen in dialysis patients [aHR 1.60 (95% CI 1.21-2.13)], and not after KT. For both outcomes, the impact of comorbidities was stronger in low-income countries. Graft survival was not affected by the presence of comorbidities [aHR for 5-year graft failure 1.18 (95% CI 0.84-1.65)]. CONCLUSIONS: Comorbidities have become more frequent in children on KRT and reduce their access to transplantation and survival, especially when remaining on dialysis. KT should be considered as an option in all paediatric KRT patients and efforts should be made to identify modifiable barriers to KT for children with comorbidities.
Keywords: chronic kidney disease; kidney transplantation; children; epidemiology; comorbidities